Impact of COBIT5 Framework Application in the Efficiency and Effectiveness of Information Technology. “An Applied Analytical study of a sample of Iraqi Private Shareholding Banks” - Abdul Ridha S. AL-Basri; Adnan Mohammmed (Journal of Techniques)
The success of the banking sector in the modern era depends on the effective and innovative use of information technology and information is one of the main resources of all institutions, and from the moment of creation of information to the moment of disposal technology plays an important role, so it requires investment and harmonization of investment in information technology and business, recently considered IT is a strategic tool for managing enterprise resources that connects stakeholders, customers, and suppliers, and promotes the conduct of various processes as quickly and efficiently as possible, and is a tool for storing and retrieving business-related information. It is important to create value, which is important for shareholders and helps in achieving the objectives of the institutions and continuity through access to efficiency and effectiveness, the problem of research shows the risks and electronic financial manipulation, which requires great attention in the field of internal control to face those risks, which is increased by increasing the use of information technology. The study used two main hypotheses. The study was applied to a community of (37) banks. A sample of (25) banks was adopted. Checklist was used to collect research data and to perform statistical analysis, SPSS-19 was used to calculate (arithmetic mean, standard deviation, coefficient of difference, relative importance, T test, F test, R2 determination factor), The results confirmed the existence of a statistically significant correlation and impact of the framework (COBIT5) as an internal control tool in the Iraqi private shareholding banks, in addition to the application of the framework (COBIT5) as an internal control tool helped in the governance and management of banks as well as maximize the value and benefit through the use of technology Information. The most important recommendations of the research, was the need for bank management attention in the implementation of the framework (COBIT5) properly and identify areas of the framework (COBIT5) that need to be improved in line with the strategic objectives of the bank.